THE EFFECTIVENESS OF ONLINE PROMOTION THROUGH INSTAGRAM SOCIAL MEDIA IN INCREASING SALES IN @ROSALINA_SHOP USING THE AIDA METHOD - Anggraeni, Weni Nur; Setianingsih, Wahyu Eko; Sumowo, Seno (Univesitas Muhammadiyah Tangerang, 2024)
This study focuses on seeing how far Instagram social media is effective as a means of promoting @rosalina_shop which is known to sell women's needs ranging from fashion to beauty products using the AIDA method. This research uses a descriptive method with a quantitative approach which explains in detail the problems studied based on data obtained through questionnaires that have been collected, and then analyzed. The primary data in this study was a questionnaire with a sample of 75 people with special criteria, namely following @rosalina_shop Instagram account and having made a one-time purchase. Based on the results of research using the AIDA method on online promotion, @rosalina_shop on social media, Instagram is included in the